2024
DOI: 10.1039/d3fo05406c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring novel Kokumi peptides in Agaricus bisporus: selection, identification, and tasting mechanism investigation through sensory evaluation and computer simulation analysis

Tao Feng,
Chenwei Ma,
Sha Chen
et al.

Abstract: Agaricus bisporus contains amino acids associated with thickness and full-mouthfeel, making it a potential candidate for salt substitutes and flavor enhancers in various food applications. Kokumi peptides were isolated from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…Chang et al 39 studied several kokumi peptides and found that hydrophobic, electrostatic, and hydrogen bonds were important for the binding of kokumi peptide and hCaSR. Feng et al 40 identified Kokumi peptide from the enzymatic degradation product of Agaricus bisporus. Sensory evaluation showed that the taste thresholds of EWVPVTK and EYPPLGR in aqueous solution were 0.6021 and 2.332 mmol/L, respectively, and EWVPVTK exhibited a higher sense of richness at a lower concentration compared with EYPPLGR.…”
Section: Analysis Of Molecular Dockingmentioning
confidence: 99%
“…Chang et al 39 studied several kokumi peptides and found that hydrophobic, electrostatic, and hydrogen bonds were important for the binding of kokumi peptide and hCaSR. Feng et al 40 identified Kokumi peptide from the enzymatic degradation product of Agaricus bisporus. Sensory evaluation showed that the taste thresholds of EWVPVTK and EYPPLGR in aqueous solution were 0.6021 and 2.332 mmol/L, respectively, and EWVPVTK exhibited a higher sense of richness at a lower concentration compared with EYPPLGR.…”
Section: Analysis Of Molecular Dockingmentioning
confidence: 99%